2021
DOI: 10.3390/biology10090834
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Subtypes and Androgen Receptor Gene Expression in Primary Breast Cancer. A Meta-Analysis

Abstract: The androgen receptor (AR) is frequently expressed in breast cancer (BC), but its association with clinical and biological parameters of BC patients remains unclear. Here, we investigated the association of AR gene expression according to intrinsic BC subtypes by meta-analysis of large-scale microarray transcriptomic datasets. Sixty-two datasets including 10315 BC patients were used in the meta-analyses. Interestingly, AR mRNA level is significantly increased in patients categorized with less aggressive intrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 64 publications
1
3
0
Order By: Relevance
“…Our findings differ from the previous study in which AR expression was found to be associated with a lower histologic grade only in ER-positive breast cancer but not in ER-negative breast cancer [ 24 ]. In PAM50 defined intrinsic subtypes, the expression of AR in basal-like subtype was less than in luminal A and luminal B subtypes which is consistent with previous studies [ 7 , 25 , 26 ]. Additionally, the correlation between the expression of AR and ESR1 was only significant in luminal A and basal-like subtype but not in luminal B and HER2-enriched subtypes.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings differ from the previous study in which AR expression was found to be associated with a lower histologic grade only in ER-positive breast cancer but not in ER-negative breast cancer [ 24 ]. In PAM50 defined intrinsic subtypes, the expression of AR in basal-like subtype was less than in luminal A and luminal B subtypes which is consistent with previous studies [ 7 , 25 , 26 ]. Additionally, the correlation between the expression of AR and ESR1 was only significant in luminal A and basal-like subtype but not in luminal B and HER2-enriched subtypes.…”
Section: Discussionsupporting
confidence: 90%
“…AR overexpression was prevalently observed in patients affected by less aggressive intrinsic molecular subtypes expressing either ER or PR and having a lower histological grade, such as Luminal A and B compared to Basal-like subtype. High AR mRNA levels can be defined as a prognostic biomarker for the detection of the less aggressive BC subtypes [ 48 ]. In the current study, the distinction of BC HER2+ in luminal and non-luminal showed that the lobular histotype is prevalent in luminal AR+ and AR− tumors compared to non-luminal subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, a classification of five surrogate intrinsic subtypes is more commonly used in clinical practice; this classification is based on the assessment of ER, PR, HER2, and the proliferation marker Ki-67 ( 14 ). The histologic and molecular features of breast cancer are summarized in Figure 1 .…”
Section: Breast Cancer Biology and Classificationmentioning
confidence: 99%
“… The figure provides a schematic representation of surrogate intrinsic BC subtypes ( 14 ), based on histologic and molecular features, which have significant implication for prognosis and treatment choice. …”
Section: Breast Cancer Biology and Classificationmentioning
confidence: 99%